GAMBARAN TINGKAT RISIKO CEDERA PADA ANAK USIA SEKOLAH - Padrizal ' Lubis; Oswati ' Hasanah; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Injury was a leading cause of death in children under the age of 18 years each year and almost 90% of these cases was account for unintentional injuries. This study was to describe injury risk level in school age children. Design of this study was descriptive study that was done in SDN 37 Pekanbaru. Sample of this study was 91 respondents form first to fifth grade based on inclusion criteria using proportional random sampling. The research was done by using questionnaire that had been tested it’s validity and reliability. The univariate analysis was conducted to know frequency distribution. The result showed most of respondents (60,4%) was in intermediate risk, 36,3% (33 respondents) was in low risk, and 3,3 % (3 respondents) was in high risk. The number of respondents who were at moderate risk level indicates that respondents often doing injury risk activities. The result of this research was recommended to the school to improve the safety of school children through education about safety, provide a safe school environment and adequate supervision. For parents to further improve the supervision of the child when the child is dealing with traffic. Keywords: injury, injury risk level, school-age children